The Effect of Problem-Based Blended Learning towards Students’ Critical and Creative Thinking Skills - Kartini, Siluh Made Surya; Widiartini, Ni Ketut; Pujawan, I Gusti Ngurah (Graduate Program Magister Manajemen Pendidikan, 2023)
The study was aimed at investigating the effect of problem-based blended learning towards students’ critical and creative thinking skills in economic learning process. Quantitative method was used as a research design by adapting quasi-experimental model. The study was conducted at SMAN 1 Marga, Tabanan, Bali by involving 43 eleventh-grade students as the research sample in which they were selected by using random sampling technique from the total 312 population. The data were obtained through post-test in which the essay test and performance test were conducted as the data collection technique. The instruments used were essay test and performance test rubric. The obtained data were analyzed descriptive and inferential statistically. ANOVA and MANOVA test were conducted to answer the hypothesis of this study. It was found that; 1) there was an effect of problem-based learning on students’ critical thinking skills, 2) there was an effect of problem-based learning on students’ creative thinking skills, 3) there was a simultaneous effect of problem-based blended learning towards students’ critical and creative thinking skills.